Women in chicken business: An ILRI innovation scaled through the Maisha Makutano TV series - Galiè, Alessandra; Campbell, Zoë A.; Jumba, Humphrey; Gichuki, Kenneth (International Livestock Research Institute, 2025)
The TV edutainment Maisha Makutano integrated the International Livestock Research Institute (ILRI) Women in Business (WiB) innovation in its 13 episodes on Kenya’s Citizen TV and YouTube in 2025. The series provided practical tips to young women vets and para/vets and farmers on how to start a new chicken business. At the same time, it addressed gender norms that are likely to restrict women from engaging in business by promoting a positive image of women agripreneurs, and by providing a role model of men who support their womenfolk in business and get empowered (rather than disempowered) as a result. Maisha Makutano reached 3.7 million viewers in each episode thereby disseminating WiB widely.